Acute Kidney Injury and Pediatric Bone Health - Hegde, Anisha; Denburg, Michelle R.; Glenn, Dorey A. (Frontiers in Pediatrics, 2021)
Acute kidney injury (AKI) has been associated with deleterious impacts on a variety of body systems. While AKI is often accompanied by dysregulation of mineral metabolism—including alterations in calcium, phosphate, vitamin D, parathyroid hormone, fibroblast growth factor 23, and klotho, its direct effects on the skeletal system of children and adolescents remain largely unexplored. In this review, the pathophysiology of dysregulated mineral metabolism in AKI and its potential effects on skeletal health are discussed, including data associating AKI with fracture risk.